Oxygen saturation and breathing patterns in infancy. 1: Full term infants in the second month of life. Issue 5 (May 1991) - Stebbens, V A; Poets, C F; Alexander, J R; Arrowsmith, W A; Southall, D P
Abstract : Overnight 12 hour tape recordings were made of arterial oxygen saturation (SaO2, pulse oximeter in the beat to beat mode) and abdominal wall breathing movement on 67 healthy, full term infants between the ages of 29 and 54 (median 39) days. The median baseline SaO2 during regular breathing was 99.8% (range 97.0-100%). Fifty four infants (81%) had shortlived episodes during which SaO2 fell to 80% or less (desaturation); the median rate was 0.9 desaturations/hour, and the median duration of each desaturation was 1.2 seconds. The 97th centile value for the duration of all episodes in which SaO2 fell to less than or equal to 80% was 4.0 seconds. The frequency of desaturations was significantly higher, and their duration significantly longer, when the breathing pattern was non-regular rather than regular. The percentage of apnoeic pauses (greater than or equal to 4 seconds in duration) followed by a desaturation was higher during non-regular than regular breathing; it was particularly high during periodic breathing. A knowledge of normal variability of baseline measurements of oxygenation and of the relationship between oxygenation and breathing patterns in infants is essential to the use of pulse oximetry in clinical practice.